From the Council of Nicaea to Vatican II: Professing the Faith, the Creeds, and the Church’ s Credibility 31st International Theological Symposium (Split, Chorwacja, 16-17.10.2025) - Wysocki, Marcin (Vox Patrum, 2025)
Report from the international conference titled From the Council of Nicaea to Vatican II: Professing the Faith, the Creeds, and the Church’ s Credibility, 31st International Theological Symposium, that took place on 16-17.10.2025 at the Faculty of Theology of the University of Split, in Croatia.